Hypothyroidism in patient with Graves disease treated with antithyroid agent: A case report - Ahmad H. Asdie, Ahmad H. Asdie (Universitas Gadjah Mada, 1993)
The paper presented a case of hypothyroidism in patient with Graves disease after have long been treated with antithyroid agent. The cause of hypothyroidism in this case might be (1) the effect of anti-thyroid agent, (2) natural history of Graves disease as a result of autoimmune mechanism, and (3) coincidental presentation of Graves disease and condition causes hypothyroidism (hashitoxicosis).A 39 year old woman, household , admitted to Sardjito Hospital because of general fatigue and facial edema. She was previously treated as Graves disease with PTU (propylthiouracil) 100 mg 3 times 100 mg/day for 2 years. Because of allergic reaction against PTU, the drug was replaced by NeomercazolÃÂ®. One year later the patient complaining body weight (BW) gain, with the laboratory investigation showed T3 = 0.78 ÃÂµg/d1 (N: 0.6-1.9); T4 = 2436 ÃÂµg/d1 (N: 45-100). Six months before admission she has not taken any drugs. On admission, BW 60 kg, other vital signs were in normal limits, palpebral edema, T3 = 0.3 itg/d1; Ta = 2.0 jig/d1; Total cholesterol 329 mg/dl; LDL-cholesterol 238 mg/dl; triglycerides 298 mg/d1; Anti-thyroglobulin 1/1280 (N: negative); anti-microsomal negative; other laboratory results revealed normal values. She was diagnosed as hypothyroidism post treatment of Graves disease. She was treated with ThyraxÃÂ® 1 tablet daily, and one year later she was in a normal condition.All patients with Graves disease should be followed up regularly eventhough the clinical condition already subsided, since other autoimmune disease may coincidentally present.Key Words: hypothyroidism Graves disease hashitoxicosis antithyroid agents autoimmune disease